PENERAPAN PASAL 59 UNDANG-UNDANGNOMOR 12 TAHUN 2008 TENTANG CALON PIMPINAN DAERAH DARI CALON PERSEORANGANDALAM PILWALI TAHUN 2013 DI KOTA KEDIRI - Zaenal Arifin (UNIVERSITAS ISLAM KADIRI, 2015)
Act of 2008 regulates the candidates for regional heads of individual candidates. This article is actually adopting a sociological developments and the insistence of the people of Indonesia who want democracy from the people by the people for the people. The desire was already accommodated in Act Number12 of 2008. The researchers used the method of normative legal research which researchesall the rules involved in the elections. In this study it can be concluded that the candidates of Mayor of Verification of Political Parties and individual Election Commission which is committed by election commission lawsin Kediri that is in conformity with that stipulated in Article 59 of Law Number 12 of 2008